(untitled) (Journal of the College of Basic Education, 2023)
In this investigation, polyammoniumphosphate (PAP) (I) and chlorinated Rubber (CR.) (II) ,were used as flame retardant for Unsaturated polyester resin in the weight ratios of 2,4,6 & 8%, by preparing films of (130×130×3) mm in diameter, Also film of Unsaturated polyester resin with mixture of [50%(PAP)+50%(CR.)] (III) in percentage of 2,4,6 & 8% by weight prepared to test the combined action .Three standard tests used to measure the flame retardation which are :1-ASTM : D-28632-ASTM : D-6353-ASTM : D-3014The results obtained from these tests indicating that , the (CR.), (PAP) and their mixture, have a good effect as flame retardants for Unsaturated polyester resin, but their combined action of them was more effective than each of them alone .Finally , the compatibility between the additives and polymer which have a clear effect on retardation